A cross-national comparison of police attitudes about domestic violence: a focus on gender. Issue 2 (15th May 2017) - McPhedran, Samara; Gover, Angela R.; Mazerolle, Paul
Abstract : Purpose: The purpose of this paper is twofold. The first goal is to conduct a cross-national examination of law enforcement officer attitudes about domestic violence (DV) by comparing officer attitudes in the USA to officer attitudes in Australia. The second goal is to examine law enforcement officer attitudes about DV using a gender lens to identify whether patterns in attitudes among male and female officers in the USA are similar to those among Australian male and female law enforcement officers. Design/methodology/approach: The current study involves a comparative analysis of DV attitudes in two different countries (the USA and Australia). Officers in the USA were asked to indicate their level agreement with 28 attitudinal statements about DV. The Australian survey adapted the Gover et al. (2011) instrument by including 24 of the 28 attitudinal statements. The survey followed a mixed-methods design with both quantitative and qualitative components. Bivariate analyses were conducted to determine whether attitudes varied by country and gender of the responding officers. Analyses of attitudinal questions and categorical variables (e.g. gender) were conducted using t -tests. Findings: According to survey data gathered from police officers in Colorado (USA) and Queensland (Australia), male and female officer attitudes within each country are more similar than different. When comparing the overall sample of American officer attitudes to Australian officer attitudes, they significantly differ about half the time. Research limitations/implications: The Australian survey had a considerably low response rate, and therefore it cannot be stated with certainty whether the responses given are truly representative of the views of Australian officers as a whole, although the demographic characteristics of the sample were comparable with the overall police population demographics. Another limitation is that not all demographic and background variables were collected by both surveys. For example, the US survey asked about officers' ethnicity, while the Australian survey did not, and the Australian survey asked about how many DV jobs officers attended per month, while the US survey did not. Practical implications: Improving knowledge about police attitudes towards DV can help to inform future policy or practice implementation, as well as training programmes and better overall responses to the pervasive and ongoing problem of DV internationally. Originality/value: This is a unique and original piece of research as it is a partial cross-national replication of an existing survey. This work does have the potential for great impact in understanding and developing innovative law enforcement responses to DV. In developing such responses officer attitudes need to be considered and integrated into the response, as their opinions will guide the support of future interventions.